First baby after 30 ... or 40? - Stanway, Penny (Orion, 1999)
One baby in ten is now born to a woman over 40, and even more than mothers aged 30-plus. Some mothers wait for career reasons, others untuk they become fertile, or meet the right man! This guide highlights the pros, cons and management of pregnancy and birth over 30... or 40. Bring yourself up to date on preparing for pregnancy and what to do if you prove less fertile than you hoped. Learn how best to look after yourself and your growing child. A practical book that anwers the questions that would-be mums and dads may not even think to ask.